Pelestarian Warisan Budaya Nasional Pencak Silat Melalui Kegiatan Ekstra-Kurikuler Sekolah dalam Mewujudkan Profil Pelajar Pancasila - Elis Lisyawati; Khairunisa; Rika Opsari; Ade Tutti (EduInovasi: Journal of Basic Educational Studies, 2025)
Education and culture are two aspects that are mutually integrated, because education is a cultural transfer process that reflects cultural values. The Industrial Revolution 4.0 has forced humans to change their behaviour, outlook and mindset to fit the times. Cultural transformation is important because if the Indonesian nation is not ready to face the Industrial Revolution 4.0, we will experience ‘turmoil’ or cultural shocks that damage the cultural values of the Indonesian nation with the ideology of Pancasila. Here the need to transform cultural values through the education process is inevitable. This research uses descriptive qualitative methods with interview techniques, observation and documentation, then in-depth analysis for data collection in order to explain how the transformation of Pencak Silat art values at SDIT Dinamika Umat Kemang Bogor West Java, able to contribute to preserving the National cultural heritage through extracurricular education through the formation of Pancasila Students who reason critically, are creative, independent, have faith, are devoted to God Almighty, have noble character, work together, and have global diversity in accordance with the vision of the Ministry of Education and Culture 2020-2024, namely realising an advanced, sovereign, independent and personalised Indonesia. Based on the findings in the field, SDIT Dinamika Umat seeks to preserve the cultural heritage of pencak silat through a form of protection that refers to the regulations and policies outlined in the extra-curricular curriculum design that is relevant to the values of Pancasila. Providing adequate facilities and facilities and presenting competent and certified trainers. The pattern of development is by designing a curriculum according to the needs and demands of the times. There is cooperation and collaboration between the government, schools and pencak silat organisations, as well as student involvement in training and competition, while its use integrates with several subjects, competitions and festivals as well as awards and achievements.